Enhancing Scientific Literacy under the PISA 2025 Framework: A Comparative Study of SQ3R and Discovery Learning Models - Alifia Rizky Nurvidian; Suwito Singgih; Rina Rahayu (Jurnal Pendidikan MIPA, 2025)
Scientific literacy is a crucial skill for students to understand scientific phenomena and make informed decisions based on evidence. However, many Indonesian students still struggle with these skills, indicating unresolved issues in the classroom implementation of scientific literacy. This study aims to address this issue by examining the effectiveness of the SQ3R (Survey, Question, Read, Recite, and Review) learning model in improving junior high school students' scientific literacy skills compared to the Discovery Learning learning model. The research design was a quasi-experimental design with a control group, and a pretest and posttest were administered. This study involved 60 eight-grade students at SMPN 1 Mertoyudan. The experimental group consisted of 30 students who received instruction using the SQ3R method, while the control group consisted of 30 students who used the Discovery Learning method. Scientific literacy skills were measured using 13 questions, which were tested for validity and reliability (α=0.935) based on the PISA 2025 science competency framework. Pretest and posttest data were analyzed using N-Gain scores and independent sample t-tests. The study showed that the SQ3R group demonstrated greater improvement in scientific literacy skills than the Discovery Learning group. The experimental group’s average score jumped from 38 on the pretest to 83 on the posttest, with an N-Gain of 0.72, which is considered high. Meanwhile, the control group’s score rose from 36 to 70, with an N-Gain of 0.52, which is considered moderate. An independent-samples t-test confirmed a significant difference between the two groups (p < 0.001). This study shows that the SQ3R learning model is superior to Discovery Learning in improving students’ scientific thinking, reading comprehension, and critical evaluation of information, essential components of scientific literacy. The structured SQ3R approach encourages active student participation and a regular observation process, making it an effective strategy for improving scientific literacy at the junior high school level.    Keywords: scientific literacy, junior high school, SQ3R, science competency, reading strategy.